Consubstantiality and Inhabitation in the Christological Thought of Hilary of Poitiers. Nicene Influence or Intimate Understanding of the Fourth Gospel? - Alba López, Almudena (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2024)
We know from Hilary of Poitiers’ own writings that he had no knowledge of the Nicaean creed until the year 356. However, in spite of this, it is obvious that Hilary of Poitiers adhered to the creed’s fundamental notions that defined correct understanding of the nature of Christ since his earliest writings. This is due to the fact that his Christological thought stems from an intimate understanding of the Gospel of John rather than a mere defense of the Nicene homousios. Through his exegesis of the most significant passages and motifs in the Fourth Gospel, Hilary of Poitiers delves into the relationship between the Father and the Son, analyzing its consubstantial nature and the mutual inhabitation of their Persons, endowing his Christological thought with a Pneumatological character. In doing so, he demonstrates a profound knowledge of the nature of Christ that goes far beyond mere speculation concerning his familiarity with the Nicaean creed and homousios.